Preparation of filamentous hemagglutinin from Bordetella pertussis and assay for serum antibodies to filamentous hemagglutinin and pertussis toxin for clinical and public health laboratories. - Wong, K H (1989)
A procedure that is sufficiently simple and economical for use in clinical and public health laboratories for producing and purifying filamentous hemagglutinin (FHA) and determining antibodies to this major antigen of Bordetella pertussis in serum is described. High yields of FHA (40 to 80 mg/liter) were obtained in the supernatant by cultivating B. pertussis in modified CL medium. The FHA antigen was separated from pertussis toxin (PT) and other antigens by chromatography on hydroxylapatite. Removal of residual PT activity in the FHA fraction was effected by affinity absorption of PT with Fetuin immobilized to Sepharose 4B. The FHA was used as the antigen for determining titers of immunoglobulin G (IgG), IgA, and IgM to FHA in sera of patients with pertussis by an improved enzyme-linked immunosorbent assay. Development of the interfering background color commonly observed in conventional FHA enzyme-linked immunosorbent assay procedures was eliminated by washing the reaction wells with a buffer of high ionic strength before adding the peroxidase conjugates. In the absence of nonspecific background color, the reaction endpoints were easy to read. The FHA prepared by the procedure described was identical to a reference preparation of purified FHA in sodium dodecyl sulfate-polyacrylamide gel electrophoresis profiles and serological specificity assays. High yields of FHA were obtained from all four strains of B. pertussis tested in this study, indicating that the procedure for enhanced production of FHA may be generally applicable to other strains of B. pertussis. Results from tests of 50 serum specimens with clinical information on pertussis for FHA and PT antibodies by the assay procedures described exemplified the usefulness and caveats of serodiagnosis for pertussis.